PWE-067 The Effect of Body Position on Baseline Oesophageal Impedance. (17th August 2016) - Bray, A; Davidson, A
Abstract : Introduction: Our initial experience with 24 hour pH-impedance (pHZ) recording revealed a higher than expected proportion of patients with extended periods of low nocturnal baseline impedance (BImp). Suspecting that this was not always caused by uncleared refluxate, we wished to investigate causes of low BImp. Our aim was to examine the effect of body position on BImp in patients with and without mucosal injury. Methods: We conducted a retrospective review of 24 hour pHZ data from all patients who have undergone testing within our facility from October 2013 to December 2015. BImp was calculated by averaging 12 × 30 second windows (one window per 2 hour segment) avoiding swallows, reflux events, meals and beverages. 1 Extent of mucosal injury was determined from gastroscopy. Results: Data from 115 patients (75 without mucosal injury and 40 with grade A to C oesophagitis or Barrett's oesophagus) were analysed. Overall BImp was dependent upon both extent of mucosal injury (decreasing with increasing mucosal injury) and distance above the lower oesophageal sphincter (LOS) (decreasing distally). In patients without mucosal injury, BImp was only channel-dependent in the upright position. In patients with mucosal injury, BImp was channel-dependent, and more so, in both positions. These results are illustrated in Figure 1 . Conclusion: The difference between upright and supine BImp in patients without mucosal injury at proximal channels may be caused by poorer contact between impedance sensors and mucosa when upright and is therefore unlikely to be clinically significant. The strong dependence of BImp upon channel in patients with oesophagitis suggests that mucosal injury worsens towards the LOS, as expected. One explanation for the difference between upright and supine BImp in these patients at 7 and 9 cm may be more uncleared refluxate at these channels whilst supine. Reference: 1 Kessing BF, Bredenoord AJ, Weijenborg PW, et al . Esophageal acid exposure decreases intraluminal baseline impedance levels. Am J Gastroenterol 2011;106 :2093–7. Disclosure of Interest: None Declared